Predicting egg size across temperatures in marine teleost fishes. Issue 5 (13th July 2020) - Anderson, David M.; Gillooly, James F.
Abstract: Marine teleost fish species in colder environments generally produce larger eggs than those in warmer environments. This pattern is thought to reflect changes in the optimal strategy of allocation to offspring size and number across temperatures, yet quantitative assessments of this hypothesis are lacking. Here, we model optimal offspring size across temperatures in marine teleost fishes based on the trade‐off between offspring survivorship and number. In doing so, we derive quantitative predictions for the relationship of optimal egg size to temperature based on the size and temperature dependences of the growth and mortality, and hence survivorship, of eggs and larvae. Our model shows that smaller eggs are favoured at warmer temperatures largely because egg survivorship declines with both egg size and temperature. The predictions of our model (egg mass in grams = 0.013* e −0.11*T ºC ) were comparable to the observed interspecific relationship (0.0029* e −0.09*T ºC ; N  = 221 spp.). Thus, our results provide insights into how temperature shapes the evolution of egg size in marine teleost fishes.